Die samestelling en struktuur van die boek Hosea - Vosloo, W. (Verbum et ecclesia, 1992)
The composition and structure of the book Hosea Notwithstanding the composition of a book as revealed by means of historical critical methods, it is necessary to establish the structure of the final text by way of literary criteria and with regard to contents. Such a structure does not necessarily represent the intention of the author(s), but represents a reader’s approach to the text. Most commentaries on the book of Hosea follow the main divisions 1-3; 4-11; 12-14, which has been demonstrated to be the result of formation and the final redactor’s activities. A more viable structure is proposed to facilitate the reading of the text.